Ketertarikan dan Persepsi Mahasiswa Fakultas Ekonomika dan Bisnis untuk Bekerja di Usaha Kecil Menengah - Etni Marliana (BISMA (Bisnis dan Manajemen), 2018)
Small and Medium Enterprises (SMEs) has exceptionally important role in Indonesian economic development. However, SMEs is facing some challenges due to lack of qualified human resources to work in this sector. This research is designed to identify the perception of business school students in working with SMEs. Futhermore, it also shows how SMEs is perceived to offer the job factors that are important for the students to dertermine a job. The sampling method used was purposive sampling method. The data were collected by primary data collection through questionnaires. Data analysis was performed with Wilcoxon Signed Rank Test. The result showed that business school students are less attracted to work with SMEs compare to large enterprises. Furthermore, students perceive that SMEs are better than large enterprises only interms of quality and managerial relationship, authority, and involvement in decision making. It is also perceived by the students that compare to large enterprise SMEs offer less job factors that are viewed to be important to determine a job.